Circular material use in landscape design - Medne, Sindija; Ulme, Andra; Zotova, Inga (Landscape Architecture and Art, 2023)
The aim of the article is to highlight trends in landscape and environmental improvement by including new environmental and landscape elements made from recycled materials. To achieve this objective, a number of objectives have been defined: to present a recycled tyre pellet material for use in outdoor landscaping, to look at the tyre recycling process and how this material is obtained, to look at and analyse market trends and products for this material, how this material fits into the circular economy, to propose new ways of using this material in environmental and landscape landscaping. The methods used in the research are literature analysis, research of examples of good practice in Europe, constructive criticism and analysis, public surveys and grapho-analytical compilation of the obtained data. An essential part of the research is the conducted experiment, as the result of that recycled tire granules were used in outdoor furniture collection. The selected research topic is actual because it is necessary to think about the wider use of recycled tire materials, to increase the use of recycled material in various outdoor environmental products, to create demand in this sector; as well as introduce more people to this material - in a different way than usual.